Unfinished business. Issue 1 (27th September 2021) - Crews, David
Abstract: At the time of my retirement there were two topics that I considered unfinished business. The first is the Evolution of Sex Differences and the second, the she‐male controversy in the Canadian red‐sided snake ( Thamnophis sirtalis parietalis ). These questions are developed in this perspective.